2016
DOI: 10.1371/journal.pone.0146141
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Bidens pilosa on Body Weight Gain, Food Conversion Ratio, Gut Bacteria and Coccidiosis in Chickens

Abstract: In the interests of food safety and public health, plants and their compounds are now re-emerging as an alternative approach to treat gastrointestinal diseases in chickens. Here, we studied the impact of the edible medicinal plant, B. pilosa, on growth performance, gut bacteria and coccidiosis in chickens. First, we found that B. pilosa significantly elevated body weight gain and lowered feed conversion ratio in chickens. Next, we showed that B. pilosa reduced cecal damage as evidenced by increased hemorrhage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 39 publications
2
49
0
Order By: Relevance
“…Apart from being one of the most predominant members of chicken microbiota [28,[33][34][35][36], Bacteroides genus may significantly contribute to the gut health of the animals. Its positive effects are related to its beneficial role for weight gain and growth performance [56] and the inhibition of Clostridium perfringens sporulation by its fermentation products [57]. Furthermore, Roseburia is a well-known butyrate-producing genus [58], thus further representing another potential beneficial bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from being one of the most predominant members of chicken microbiota [28,[33][34][35][36], Bacteroides genus may significantly contribute to the gut health of the animals. Its positive effects are related to its beneficial role for weight gain and growth performance [56] and the inhibition of Clostridium perfringens sporulation by its fermentation products [57]. Furthermore, Roseburia is a well-known butyrate-producing genus [58], thus further representing another potential beneficial bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…First, the data in a previous publication 9 and this work suggest that BP interferes with but does not kill Eimeria species. Second, BP contributes to growth performance and anticoccidial control in chickens plausibly via modulation of gut microbiota including increased probiotics and decreased detrimental bacteria 15 . The compounds in BP that are active against eimeriosis have not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we have shown that BP reduced infection and drug resistance of Eimeria in chickens at the laboratory scale 9 . Further, BP increased beneficial bacteria species and decreased harmful bacteria species in the guts of chickens, probably accounting for part of its anticoccidial action 15 . In this study, to further evaluate its anticoccidial efficacy under intensive farming conditions, a field trial of BP was conducted on an organic chicken farm.…”
mentioning
confidence: 99%
“…Recently, plant Bidens pilosa was used in diet of birds, which significantly elevated body weight gain and lowered feed conversion ratio. Also, B. pilosa reduced cecal damage, villus destruction and decreased villus-tocrypt ratio in chicken ceca [35,36]. Table 3 shows some compounds related to different action to control avian coccidiosis.…”
Section: Essential Oilsmentioning
confidence: 99%